Isolation and identification of eurycomanone from akar pasak bumi (Eurycoma longifolia, Jack) and its antiangiogenic activity - Sugiyanto .; Nina Salamah; Mae Sri Hartati; Farida Hayati; Pinus Jumariyatno (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Pasak bumi is one of the Indonesian original plants having anti cancer activity. One compound of akar pasak bumi, i.e eurycomanone was proven to have cytotoxic effect on cancer cell culture by apoptosis induction on HeLa cells. Therefore, this study was aimed to isolate and identify euycomanone from akar pasak bumi and to look at the anti angiogenic activity of the compounds on corio alantois membrane (CAM) of chicken embryo induced by bFGF.The akar pasak bumi was ground and was macerated with methanol. The macerate was fractioned by mean of VLC. Six fractions was obtained. The second fraction exhibited two spots on a TLC system, one spot was cochromatographed with eurycomanone as the reference standart and another spot exhibited blue fluorecence at 254 nm. This second fraction, then, was chromatographed on a preparative scale TLC to separate isolate A. Anti angiogenic test was performed for Isolate A at concentration series of 5, 10, 15, 20, 40 μg/mL respectively. Egg embrio (8-9 days) were divided into 8 groups. The first group was implanted paper disc only, the second group were given bFGF on Tris HCl buffer and the third group were given bFGF (on Tris HCl buffer) + 0,8 % DMSO. The fourth to eighth group were induced by 10 ng bFGF and the test preparation at the respective concentration. After incubation at 39 °C for 3 days, each egg was opened, the content of each was aspired and discarded, the CAM sticked to its shell was examined macroscopically and microscopically for the formation of new blood vessels.Based on spectral data of UV, IR, 1H NMR, 13C NMR and MS of isolate A and comparison with the spectral data of the standart, the isolate A was eurycomanone. Eurycomanone inhibited angiogenesis at concentration of 10 μg/mL.Key words: antiangiogenic, angiogenesis, E.longifolia, eurycomanone,CAM.